Upaya Peningkatan Hasil Belajar Biologi Siswa yang Diajarkan dengan Model Pembelajaran Berdasarkan Masalah pada Sub Konsep Struktur dan Fungsi Jaringan Hewan di Kelas XI SMA Negeri 1 Meulaboh - Asiah Asiah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
The study of learning model based on  problem instruction is aimed to improve learning output in animal structure and tissue function in class XI SMA I Meulaboh. The population is all of students from class XI consisting of 5 classes and 184 students. Five students was taken from each class as the sample based on the result of the examination which is lower than SKBM (equivalen with 65 in Meulaboh). The data was collected by giving pretest and postest. T-test on level α= 0,05 was obtained t-score = 29,7 and t-table = 1,71. It revealed that t-score t-table, so that the HA was accepted. The activity of the  teachers and students in learning process has done about 81,7 % and 94,6 % which was in good catagory. The students has completed the learning process in that sub concept.